2007
DOI: 10.1371/journal.pbio.0050072
|View full text |Cite|
|
Sign up to set email alerts
|

Modification of a Hydrophobic Layer by a Point Mutation in Syntaxin 1A Regulates the Rate of Synaptic Vesicle Fusion

Abstract: Both constitutive secretion and Ca2+-regulated exocytosis require the assembly of the soluble N-ethylmaleimide–sensitive factor attachment protein receptor (SNARE) complexes. At present, little is known about how the SNARE complexes mediating these two distinct pathways differ in structure. Using the Drosophila neuromuscular synapse as a model, we show that a mutation modifying a hydrophobic layer in syntaxin 1A regulates the rate of vesicle fusion. Syntaxin 1A molecules share a highly conserved threonine in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 64 publications
2
58
1
Order By: Relevance
“…In the original paper (Littleton et al, 1998), the syx 3-69 T254I mutation was shown to block SV exocytosis because of a failure to form 7S SNARE complexes. In stark contrast, the new syx study (Lagow et al, 2007) utterly contradicts the earlier report, showing that the mutant T-I substitution confers a dominant positive effect on Syntaxin-1A, promoting 7S-SNARE-complex formation and increasing SV fusion. This is not at all compatible with an additive defect with rbo ts in blocking SV exocytosis.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…In the original paper (Littleton et al, 1998), the syx 3-69 T254I mutation was shown to block SV exocytosis because of a failure to form 7S SNARE complexes. In stark contrast, the new syx study (Lagow et al, 2007) utterly contradicts the earlier report, showing that the mutant T-I substitution confers a dominant positive effect on Syntaxin-1A, promoting 7S-SNARE-complex formation and increasing SV fusion. This is not at all compatible with an additive defect with rbo ts in blocking SV exocytosis.…”
Section: Discussioncontrasting
confidence: 94%
“…Moreover, rbo ts ;syx 3-69 double mutants displayed a severe synergistic defect in FM endocytosis at permissive temperature. These new results, together with those of Lagow et al (Lagow et al, 2007) lead us to conclude that there is a requirement for RBO in endocytosis, which becomes more demanding in rbo ts ;syx 3-69 double mutants owing to an increased need to recycle SVs to keep up with increased fusion rate.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…A structure-function study of a SNARE complex with a single site mutation near the C-terminal end of the syntaxin SNARE motif is also consistent with a lower stability and folding rate of the C-terminal compared to the N-terminal end of SNARE complex formation (35). The layer ϩ7 T254I mutation enhances constitutive and evoked fusion and also changes the structure to one that is more similar to SNARE complexes associated with constitutive fusion.…”
Section: Helix I As a Nucleation Site For Trans-snare Complex Formation?mentioning
confidence: 57%
“…The ϩ7 layer of the SNARE complex has been proposed to be one of the key differences between SNARE complexes that fuse constitutively and those that undergo triggered fusion (24). For Drosophila SNAREs, the T254I mutation enhances both constitutive and evoked neurotransmitter release, suggesting that the tighter packing of isoleucine promotes SNARE formation and fusion, whereas the presence of threonine prevents good packing (Fig.…”
Section: Resultsmentioning
confidence: 99%